Application of a cement–clay–air foam mixture as a lightweight embankment material for construction on soft clay - Salisa Chaiyaput; Jiratchaya Ayawanna; Pornkasem Jongpradist; Hatairat Poorahong; Raksiri Sukkarak; Pitthaya Jamsawang (Case Studies in Construction Materials, 2023)
Lightweight air foam materials can be used in pavement structures, for example, as embankments and subbase and base layers. Soft clay can be mixed with cement and air foam to generate a lightweight material. However, most previous studies have presented only laboratory test results for these materials and have not shown real-world applicability. The current study aims to demonstrate the application of a cement–clay–air foam mixture as a lightweight embankment material to reduce the settlement of soft Bangkok clay foundations induced by embankment weight. An experimental investigation to determine unconfined compressive strength (qu) was initially conducted in the laboratory to establish the ideal quantities of soft clay, air foam, and ordinary Portland cement required for embankment construction using the clay mixture. A full-scale lightweight embankment of area 14 m × 14 m and height 2.5 m was constructed on an 11 m thick soft clay layer to observe embankment settlement behavior on the soft clay foundation. The qu values of the lightweight materials obtained from the site were 1.3–1.8 times higher than those in laboratory tests. The mixtures with wet field unit weights of 0.6, 0.8, and 1.0 kN/m3 exhibited qu values of 430–620 and 770–1000 kPa, respectively, higher than the standard requirements (> 100 kPa for 7 curing days and > 200 kPa for 28 curing days). Based on monitored data, the lightweight embankment reduced settlement by as much as 80 % compared with a traditional embankment. Therefore, lightweight clay materials are recommended for use in the construction of road embankments on soft clay.
Keywords: Geotechnical Engineering and Soil Stabilization; Grouting, Rheology, and Soil Mechanics; Innovative concrete reinforcement materials